A Comparative Analysis of Various Chaotic Genetic Algorithms for Multimodal Function Optimization - Yap, David F. W. (2012)
This study proposes a novel method of introducing chaotic induced genes into Genetic Algorithms (GA) in order to solve unimodal and multimodal mathematical test functions. The integration of chaotic elements based on logistic map into GA has significantly improved the accuracy in the aspect of the best fitness value. Simulation results show that the influence of Chaos theory does improve the optimization accuracy of the mathematical functions used.